Pendampingan Manajemen Keuangan Usaha Dan Penguatan Kemitraan Bahan Baku Pada UMKM Kopi Manggis Lombok - I Nengah Arsana; Putri Reno Kemala Sari; Rusdi; Syaiful Amri (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
This community service program is a follow-up to a previous mentoring activity on product development and marketing strategy for a mangosteen coffee MSME in Lombok. While the previous stage focused on the market side of the business, this stage addresses the internal side, namely, business financial management and the strengthening of raw material partnerships with local farmers. The methods used include a community socialisation session involving residents and coffee farmers, on-site business consultations, and intensive mentoring sessions covering the separation of business and household finances, simple bookkeeping, cost of production calculation, pricing, and raw material inventory management. The results show that the partner can record transactions consistently, understand the cost structure of each product variant, set prices based on cost calculation, and build a clearer supply arrangement with local farmers. These improvements complement the marketing capacity built in the previous stage and strengthen the overall sustainability of the partner's business.